Soil Temperature Measurements, 2019–2023, Turkana Basin Institute Research Centers, Kenya - Mae Saslaw; Gregory A Henkes; Daniel Green; Martin Kirinya; Melissa Boyd; Kevin Hatton; Harrison Ngumbau; Hezekiah Mwangombe (PANGAEA, 2025)
Soil temperatures were recorded using HOBO Pendant Temperature Data Loggers buried at Turkana Basin Institute (TBI) Research Centers from 2019–2023. Twelve loggers were deployed at TBI-Ileret beginning in September 2019 through January 2021. Four were buried in full sun at 10, 30, 60, and 90 cm depths, another four under shade cover of thick brush, and three in a partially shaded location at 10, 30, and 60 cm. Six loggers were buried at TBI-Turkwel in January 2020 through February 2021 at 10, 30, and 50 cm under sun and shaded conditions. The second deployment began in July 2021 at both research centers, including sun and shade profiles at Turkwel and a full sun profile at Ileret. A third deployment using the same profiles at both sites followed shortly after the second, from June 2022 until early July 2023. Sensor battery failure occurred part way through the data collection periods on several sensors during each deployment, resulting in incomplete records for some depth-condition combinations.